Fermented foods, the gut and mental health: a mechanistic overview with implications for depression and anxiety. (1st September 2020) - Aslam, Hajara; Green, Jessica; Jacka, Felice N.; Collier, Fiona; Berk, Michael; Pasco, Julie; Dawson, Samantha L.
Abstract : Mental disorders including depression and anxiety are often comorbid with gut problems, suggesting a bidirectional relationship between mental health and gut function. Several mechanisms might explain this comorbidity, such as inflammation and immune activation; intestinal permeability; perturbations in the hypothalamic–pituitary–adrenal axis; neurotransmitter/neuropeptide dysregulation; dietary deficiencies; and disturbed gut microbiome composition. The potential of modulating the microbiome–gut–brain axis, and subsequently mental health, through the use of functional foods, is an emerging and novel topic of interest. Fermented foods are considered functional foods due to their putative health benefits. The process of microbial fermentation converts food substrates into more nutritionally and functionally rich products, resulting in functional microorganisms (probiotics), substrates that enhance proliferation of beneficial bacteria in the gut (prebiotics), and bioactive components (biogenics). These functional ingredients act biologically in the gastrointestinal tract and have the ability to modify the gut microbiota, influence translocation of endotoxins and subsequent immune activation, and promote host nutrition. This narrative review explores the theoretical potential of the functional components present in fermented foods to alter gut physiology and to impact the biological mechanisms thought to underpin depression and anxiety. Pre-clinical studies indicate the benefits of fermented foods in relieving perturbed gut function and for animal models of depression and anxiety. However, in humans, the literature relating to the relevance of fermented food for treating or preventing depression and anxiety is sparse, heterogeneous and has significant limitations. This review identifies a critical research gap for further evaluation of fermented foods in the management of depression anxiety in humans.